Drugs and Human Behavior Biopsychosocial Aspects of Psychotropic Substances Use - De Micheli, Denise; Andrade, André Luiz Monezi; Reichert, Richard Alecsander; Silva, Eroy Aparecida da; Pinheiro, Bruno de Oliveira; Lopes, Fernanda Machado (Springer International Publishing : Imprint: Springer, 2021)
XV, 568 p. 29 illus., 14 illus. in color.